The Relationship Between Basic Psychological Needs and Academic Burnout in Medical Students - Amene Markoubi; Majid Sadoughi (Kerman University of Medical Sciences, 2018)
Background Academic burnout has several negative consequences such as decreased motivation, academic eagerness, and achievement among students. Objectives The current study aimed to investigate the relationship between basic psychological needs and academic burnout. Methods The current descriptive-correlational study was conducted among 233 students of Kashan University of Medical Sciences (140 females and 93 males) selected through stratified multistage sampling in the second semester of the 2016 - 2017 academic year. The participants responded to Breso Academic Burnout and Gagné Basic Psychological Needs questionnaires and provided their demographic information. Data were analyzed using SPSS (Version 22) using canonical correlation analysis. Results There was a significant negative correlation between academic burnout and autonomy (r = -0.296, P < 0.01), competence (r = -0.548, P < 0.01), and relatedness (r = -0.290, P < 0.01) needs. Canonical correlation coefficient was 0.61. The results of canonical analysis showed only one significant set of basic psychological needs and components of burnout. In addition, as psychological needs, especially the competence need, were satisfied more, the probability of academic burnout, especially in the academic inefficacy dimension, as the main component of academic burnout, was reduced. Conclusions The fulfillment of basic psychological needs, especially competence need, plays an important role in preventing academic inefficacy among students. Fulfilment of basic psychological needs in educational programs could be a protective factor against students' academic burnout and improve their academic performance.